Experimental investigation on performance, combustion and emission characteristics of DI diesel engine using algae as a biodiesel - Mohankumar Subramaniam; Jenoris Muthiya Solomon; V. Nadanakumar; Shridhar Anaimuthu; Ravishankar Sathyamurthy (Energy Reports, 2020)
Diesel Powered engines are predominately used in transport and power generators. Due to rapid depletion of fossils fuels like diesel, there is need to find alternate resources for as a fuel for transport and power sector. The use of third generation fuels like algae seems to be a promising solution to satisfy our energy demands in future. In these work algae is used as an alternative fuel with different blend combination with diesel and the results obtained are summarized. Algae fuel is blended with diesel on a volume basis, namely A10, A20, A30, A40 and A100 and made to run in diesel engines. The properties of the fuels were found according to American Society for Testing and Materials standards. Experimental testing was carried out in a single cylinder direct injection diesel engine. Among the various blends tested A20 shows closer estimation with diesel results in higher thermal efficiency lower HC, CO, Smoke and particulate matter emissions. However, the other emissions like Nitrous oxide and carbon dioxide were shown marginally higher. Regarding cylinder pressure and heat release rate curves, the peak value obtained is considerably lower at higher load condition while compared with diesel.
Keywords: 330; Algae; Biodiesel; Diesel engine; Emissions